CROSS-BORDER GREEN CARE CLUSTER YLITORNIO – ÖVERTORNEÅ: CHALLENGES AND OPPORTUNITIES - Sturk, Jenna (Rovaniemen ammattikorkeakoulu, 2013)
The purpose of the thesis was to find if there is an interest for businesses in the cross-border municipalities, Ylitornio in Finnish Lapland and Övertorneå in Swedish Norrbotten, to create a cross-border Green Care Cluster and to find the challenges for it and also to recognise the opportunities that could improve the cross-border interaction. The region for research was chosen since it is the hometowns of the author. Green Care is a new concept in tourism and therefore scarce information about the topic is available. The main concept for Green Care is to increase physical and mental well-being through nature-based products and services. In this research Green Care was supported by sustainable tourism, well-being tourism and authenticity. Qualitative research methods were used in the thesis project, semi-structured interviews and also qualitative content analysis of the collected data. The interviews conducted were individual face-to-face interviews which took place in October 2013. Findings from the examined interviews expressed the desire from both countries businesses to increase the cooperation between the tourism actors. Yet, nothing has happened since there is no driving force to push it forward at the moment. Also the interest for a Green Care Cluster was grand between the actors. Everyone was interested in participating though two businesses felt their participation was not relevant at the moment but certainly in the near future. The interest to use coopetition as an approach in the cluster seemed positive however, with clear regulations in which areas cooperation or competition is used. As for the opportunities the municipalities may sponsor the cluster in the future for it to expand to the whole Torne Valley region.